Дослідження репаративної дії мазі зі шроту листя вільхи клейкої = Studying of reparative effect of ointment with groated leaves of Alnus glutinosa = Исследование репаративного действия мази из шрота листьев ольхи клейкой - Volkovoy, V. A.; Bahlai, T. O.; Fegchenkova, Y. A.; Masliy, Y. S.; Fomina, G. P. (Journal of Education, Health and Sport, 2017)
Volkovoy V. A., Bahlai T. O., Fegchenkova Y. A., Masliy Y. S., Fomina G. P. Дослідження репаративної дії мазі зі шроту листя вільхи клейкої = Studying of reparative effect of ointment with groated leaves of Alnus glutinosa = Исследование репаративного действия мази из шрота листьев ольхи клейкой. 2016;6(11):649-656. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.207602 http://ojs.ukw.edu.pl/index.php/johs/article/view/4076 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 30.11.2016. УДК: 615,276:582.632.1 ДОСЛІДЖЕННЯ РЕПАРАТИВНОЇ ДІЇ МАЗІ ЗІ ШРОТУ ЛИСТЯ ВІЛЬХИ КЛЕЙКОЇ В. А. Волковой, Т. О. Баглай, Ю. А. Федченкова, Ю. С. Маслій, Г. П. Фоміна Національний фармацевтичний університет, Харків, Україна Резюме Вивчено вплив мазі зі шроту листя Вільхи клейкої на репаративні процеси асептичних лінійних ран шкіри. Встановлено, що мазь зі шроту листя Вільхи клейкої збільшує міцність післяопераційного рубця асептичних ран і має вищу репаративну активність, ніж препарат порівняння мазь «Вундехіл». По відношенню до контролю мазь зі шроту листя Вільхи клейкої проявляє репаративну активність 52,7 %, а «Вундехіл» 30,6 %, по відношенню до препарату порівняння ‒ вищу в 1,7 раз. За допомогою гістоморфологічного дослідження асептичних лінійних різаних ран шкіри під впливом мазі зі шроту листя Вільхи клейкої встановлено збільшення активності фібробластів у порівнянні з інтактними тваринами. Ключові слова: мазь зі шроту листя вільхи клейкої, репаративна активність, асептичні рани, тензіометрія. STUDYING OF REPARATIVE EFFECT OF OINTMENT WITH GROATED LEAVES OF ALNUS GLUTINOSA V. A. Volkovoy, T. O. Bahlai, Y. A. Fegchenkova, Y. S. Masliy, G. P. Fomina National University of Pharmacy, Kharkiv, Ukraine Abstract The effect of the ointment with groated leaves of Alnus glutinosa on the reparative processes of aseptic linear cut wounds of the skin were studied. Increase the strength of postoperative scar of aseptic skin wounds and higher restorative activity than comparator ointment «Vundehil» were founded in ointment with groated leaves of Alnus glutinosa. Reparative activity of ointment with groated leaves of Alnus glutinosa appears in 52.7% and compared to control group that it exceeds the comparison («Vundehil» 30.6 %) 1.7 times. Increased activity of fibroblasts compared to intact animals were founded by means of histomorphological study of aseptic linear cut wounds of the skin under the influence of ointment with groated leaves of Alnus glutinosa. Keywords: ointment with groated leaves Alnus glutinosa, reparative effect, aseptic linear cut wounds of the skin, tensiometry. ИССЛЕДОВАНИЕ РЕПАРАТИВНГО ДЕЙСТВИЯ МАЗИ ИЗ ШТРОТА ЛИСТЬЕВ ОЛЬХИ КЛЕЙКОЙ В. А. Волковой, Т. А. Баглай, Ю. А. Федченкова, Ю. С. Маслий, Г. П. Фомина Национальный фармацевтический университет, Харьков, Украина Резюме Изучено влияние мази из шрота листья Ольхи клейкой на репаративные процессы асептических ран кожи. Установлено, что мазь из шрота листья Ольхи клейкой увеличивает прочность послеоперационного рубца асептических ран и имеет высшую репаративную активность, нежели препарат сравнения мазь «Вундехил». По отношению к контролю мазь из шрота листья Ольхи клейкой проявляет репаративную активность в 52,7 %, по отношению к препарату сравнения ‒ высшую в 1,7 раз. При помощи гистоморфологического исследования асептических линейных резанных ран кожи под воздействием мази из шрота листья Ольхи клейкой установлено увеличение активности фибробластов в сравнении с интактными животными. Ключевые слова: мазь из шрота листьев Ольхи клейкой, репаративная активность, асептические раны, тензиометрия.